2014
DOI: 10.1093/jisesa/ieu062
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Expression Analysis of QM-Like Gene From Spodoptera litura After Challenge by the Entomopathogenic Fungus Nomuraea rileyi

Abstract: A partial sequence of QM homologue was isolated from a Spodoptera litura fatbody suppression subtractive hybridization library. The full-length Spodoptera litura QM ( SpLQM ) cDNA of 838 bp contains a 5′ untranslated region (UTR) of 112 bp, a 3′ UTR of 66 bp, and an open reading frame of 660 nucleotides coding for a 219 amino acid peptide with a molecular weight of 25.5 kDa. Analysis of SpLQM sequence revealed the presence of characteristic motifs, including the ribosomal protein L10 signature and SH3-binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…The quicker response of BmQM to fungus may be related to the rapid secretion of QM proteins involved in the primary humoral immune phase of the PO cascade system. Similarly, in S. litura , the expression of SpLQM increased faster in haemocytes than in fat bodies after entomopathogenic fungus Nomuraea rileyi challenge (Li et al ., ). Although the activation level and sensitive time of BmQM are inconsistent when confronted with different microorganisms, the results suggested that the BmQM gene is involved in insect immune response.…”
Section: Discussionmentioning
confidence: 98%
“…The quicker response of BmQM to fungus may be related to the rapid secretion of QM proteins involved in the primary humoral immune phase of the PO cascade system. Similarly, in S. litura , the expression of SpLQM increased faster in haemocytes than in fat bodies after entomopathogenic fungus Nomuraea rileyi challenge (Li et al ., ). Although the activation level and sensitive time of BmQM are inconsistent when confronted with different microorganisms, the results suggested that the BmQM gene is involved in insect immune response.…”
Section: Discussionmentioning
confidence: 98%